(untitled) (ASEAN Engineering Journal, 2012)
Glue-laminated (glulam) bamboo potentially used to be a substitute for wood as a building material, because it can be produced within four to five years of planting. Mechanical properties of glulam bamboo should be well understood by support the wider application of this new material in structural components. This study focused on embedding strength evaluation of glulam bamboo, were required to evaluate lateral resistance of dowel-type joints. The evaluation was carried out using experiment according to ASTM D5764 and numerical analysis performed with ADINATM. Material were considered in the experiment consist of bolt 12.2 mm diameter, a range of specific gravity of glulam bamboo from 0.57 to 0.79 and moisture contents varies from 11.14% to 12.45% were considered in the experiment. There were three groups of specimens: group A parallel loading to grain radial; group B parallel loading to grain tangential; and the last was group C perpendicular loading to grain. Glulam bamboo were modeled as an orthotropic nonlinear material whiles the dowel was assumed as perfectly rigid material. Contact condition between dowel and laminated bamboo was considered and the numerical model was solved under the plane stress assumption with deformation control. The experimental result was indicated that embedding strength parallel to grain (group A and B), it was significantly higher than group C. This phenomenon was apparent in the numerical study as well. The embedding strength of laminated bamboo (Fe) could be well predicted as 78.4G for parallel to grain radial, 72.79G for parallel to grain tangential; and 69.96G for perpendicular to grain radial, where G is the specific gravity.